Malthus and Verhulst models and its extensions: An application in the population growth of maned wolves - Mei, Camila; Santo Pedro Simões, Francielle (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2023)
In this article, we will explore population models generated from the classic Malthus and Verhulst models. These models are usually modeled by ordinary differential equations and the population growth rate depends on the population density. The purpose of this work is to study how small changes in the growth rate of the classic Malthus and Verhulst models results in new models. As very complex models of differential equations do not have an analytical solution, we will make a qualitative study of the solutions and observe similarities and main characteristics. Finally, we model the population growth of maned wolves.
Keywords: Malthus model.; Verhulst model.; Population dynamics.; Qualitative analysis.; Maned wolves.